ANALISIS VITAMIN C EKSTRAK ETANOL DAUN KELOR (Moringa oleifera Lam.) DAN FORMULASINYA DALAM SEDIAAN SABUN MANDI TRANSPARAN - Beta Ria Erika Marita Dellima; Eni Kartika Sari (Jurnal Jamu Kusuma, 2022)
Vitamin C merupakan salah satu kandungan fitokimia daun kelor. Vitamin C mempunyai manfaat sebagai antioksidan dan dapat mencerahkan kulit. Manfaat vitamin C bagi kulit menjadikan alasan penggunaan vitamin C dalam formulasi produk perawatan kulit. Salah satu produk perawatan kulit yang sering digunakan adalah sabun mandi. Penelitian ini bertujuan untuk analisis kuantitatif vitamin C dalam ekstrak etanol daun kelor serta aplikasinya dalam formulasi sabun padat transparan. Analisis kuantitatif vitamin C dalam ekstrak etanol daun kelor menggunakan metode iodimetri. Berbagai konsentrasi ekstrak etanol vitamin C kemudian diformulasikan ke dalam bentuk sediaan sabun mandi transparan. Sabun mandi transparan kemudian diuji organoleptis, pH dan tinggi busa. Kadar vitamin C dalam ekstrak etanol daun kelor adalah 0,162 + 0,0402 % b/b. Hasil pengujian sifat fisik sediaan menunjukkan semua formula memenuhi persyaratan. Kata kunci: ekstrak, daun kelor, vitamin C, sabun Vitamin C is one of the phytochemical constituents of Moringa leaves. Vitamin C has benefits as an antioxidant and can brighten the skin. The benefits of vitamin C for the skin are the reasons for using vitamin C in the formulation of skin care products. One of the most frequently used skin care products is body wash. This study aims to quantitatively analyze vitamin C in the ethanol extract of Moringa leaves and its application in transparent solid soap formulations. Quantitative analysis of vitamin C in the ethanol extract of Moringa leaves using the iodimetric method. Various concentrations of the ethanol extract of vitamin C were then formulated into transparent bath soap dosage forms. The transparent bath soap was then tested for organoleptic, pH and foam height. The level of vitamin C in the ethanol extract of Moringa leaves was 0.162 + 0.0402% w/w. The results of testing the physical properties of the preparations showed that all formulas met the requirements. Keywords: extract, moringa leaves, vitamin C, soap